Monitoring of Mycotoxigenic Fungi in Fish Farm Water and Fumonisins in Feeds for Farmed Colossoma macropomum - Juliana Sousa Terada-Nascimento; Jerônimo Vieira Dantas-Filho; Bruna Lucieny Temponi-Santos; Vinícius Perez-Pedroti; Maria Mirtes de Lima Pinheiro; Ricardo Ysaac García-Nuñez; Igor Mansur Muniz; Átila Bezerra de Mira; Elica Amara Cecilia Guedes; Sandro de Vargas Schons (Toxics, 2023)
This study aimed to evaluate the occurrence of mycotoxigenic fungi in fish farm water and mycotoxins in feeds for farmed tambaqui (Colossoma macropomum). A total of 40 samples of freshwater from fish farms and 16 samples of feed were collected and analyzed for microbiology. A total of five species of free-living fungi were identified in fish farms: Aspergillus fumigatus, Penicillium citrinum, P. implicatum, Fusarium oxysporum and Alternaria alternata. These fungi species were counted in water samples at 35.14 CFU mL−1 and 24.69 CFU mL−1 in the dry seasons. In all fish farms, there was a higher abundance of fungi species in the rainy season. During visits to the fish farmers, it was possible to verify poor feed storage conditions. Concerning mutations in blood cells, in tambaqui (C. macropomum), a total of 159 anomalies were found, and in Leptodactylus petersii, 299 anomalies were found, with higher incidences in conditions above 1.0 CFU mL−1 in log10(x+1) fungi and in the rainy season. The occurrence of mycotoxicological contamination was confirmed in 81.25% of the analyzed samples. The quantified mycotoxin was Fumonisins B1 + B2 (375 to 1418 μg kg−1). Pearson’s correlation analysis showed a significant positive correlation between Fumonisins and feed samples (r = 0.83). There was also a significant positive correlation between the abundance of fungi in water and the quantification of Fumonisins (r = 0.79). Based on the results obtained, it can be concluded that free-living fungi can be used as bioindicators of water quality in fish farms. Consequently, the lack of good management practices caused microbiological contamination of the aquatic environment.